Investigating Physiotherapy Management of Patients Undergoing Upper Abdominal Surgery at Waitemata District Health Board - Owens, Victoria (Auckland University of Technology, 2021)
Post-operative pulmonary complications are one of the main complications following abdominal surgery (Patel et al., 2016), closely followed by cardiac complications (Jin et al., 2014) or wound infections (De Avila & Fenili, 2017). These complications increase hospital length of stay and mortality rates (Scholes, Browning, Sztendur, & Denehy, 2009). This, in turn, imposes a significant financial burden on healthcare resources and patient recovery (Perilli et al., 2018). Physiotherapy aims to prevent and remediate postoperative complications, including PPC’s, in patients undergoing major abdominal surgery (Boden et al., 2018). As part of a larger multicenter international observational study, North Shore Hospital has collected data from 100 patients relating to the prevalence of postoperative complications and provision of physiotherapy. This nested study will enable North Shore Hospital to determine its postoperative complication rate, audit interventions to prevent these, and determine physiotherapy interventions utilised in patients undergoing major abdominal surgery. In turn, this will guide a review of our service provision and inform a change of policy where/if needed.
Keywords: Post-operative pulmonary complications; Abdominal surgery; Physiotherapy; PPC